A 56-year-old man with necrotizing pneumonia multidrug-resistant successfully treated surgically - Alencar, Julio; Ward Abdalla Maia, Ian; Wasum Mariani, Alessandro (LAJEC - Latin American Journal of Emergency Care, 2024)
Pneumonia caused by multidrug-resistant pathogens is increasing, and these infections are negatively associated with patient outcomes. Optimization of antibiotics has been suggested as a key intervention to improve clinical results, however what to do when there is no antibiotic treatment available? This case reports a 56-year-old man who developed necrotizing pneumonia due to multidrug- resistant Acinetobacter baumanni after infection with SARS-COV-2 and the use of high doses of corticosteroids. Video-assisted thoracoscopic surgery has been established as an effective and potentially less morbid alternative to open thoracotomy.